LANDFILL LEACHATE TREATMENT USING UPFLOW ANAEROBIC SLUDGE BLANKET REACTOR ENHANCED WITH SEAWEED EXTRACT BEADS - SIVATHASS BANNIR SELVAM, 1986-; C. Shreeshivadasan, supervisor 610704; Mohd. Fadhil Md. Din supervisor 283389; Norazli Othman, supervisor 580264; UTM RAZAK School of Engineering and Advanced Technology 601487 (2017)
Thesis (PhD)-Universiti Teknologi Malaysia, 2017